Leaflet-based preoperative education, knowledge, and anxiety among patients undergoing spinal anesthesia - Bella Yunita Tri Lestari; Cahaya Nugraheni; Ratih Kusuma Dewi (JOURNAL OF Mental Health Concerns, 2026)
Background: Patients undergoing spinal anesthesia are at risk of experiencing anxiety because they remain conscious throughout the surgical procedure. A lack of understanding regarding medical procedures may trigger fear and stress responses that affect both the physiological and psychological conditions of patients. Uncontrolled anxiety may disrupt hemodynamic stability and delay recovery. Limited information can also reduce patient cooperation during treatment. Preoperative education is therefore needed to improve patient knowledge and reduce anxiety, one of which can be delivered through leaflets/leaflet-based education that presents information in a concise, clear, and easily understandable format. Purpose: To examine the effect of leaflet-based preoperative education on patients' knowledge and anxiety levels among individuals undergoing surgery with spinal anesthesia. Method:  A quantitative pre-experimental design with a one-group pretest–posttest approach. A purposive sampling technique was used to recruit 68 respondents. Data were collected using a knowledge questionnaire and the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data were analysed using the Wilcoxon signed-rank test with a significance level of α = 0.05. Results: The findings demonstrated an increase in patients' knowledge and a decrease in anxiety levels following leaflet-based preoperative education. Before the intervention, most respondents had poor knowledge and moderate to severe anxiety levels. After the intervention, respondents showed improved knowledge and reduced anxiety levels. The Wilcoxon signed-rank test yielded a statistically significant difference in both knowledge and anxiety scores before and after the intervention (p < 0.001). Conclusion: Leaflet-based preoperative education significantly improves patients' knowledge and reduces anxiety levels among individuals undergoing spinal anesthesia. Keywords: Anxiety; Knowledge; Leaflet Education; Preoperative; Spinal Anesthesia.